Pollution Control and Waste Management - Sumathipala, W.L. (My University, 2012)
The magnitude of degradation of the environment increased tremendously with the industrial revolution which started in 1850s. Even prior to the industrial revolution, pollution due to human activities existed but in a reduced amount. Those days the assimilation capacity of the environment was greater than the release of pollutants in to the environment. Large volumes of wastes were released in to the environment with the development of machine-based industries. Then the assimilation capacity of the environment became lower than the rate of waste generation. As a result wastes accumulated in the environment giving rise to problems, which threatens the life existence on planet Earth. In order to control pollution, proper and appropriate legislation, emission and effluent standards for industries are essential. Awareness creation among the general public and making the man more environment friendly is an over all approach for environment protection.
Pollution Control and Waste Management Dr. W.L. Sumathipala Senior Lecturer The Open University of Sri Lanka & Director National Ozone Unit, Ministry of Environment
Keywords: pollution; environment